The effect of variation in mass flow rate and solar irradiance on temperature uniformity and thermal performance of photovoltaic thermal: A simulated CFD study - Mohd Rosli, Mohd Afzanizam; Latif, Irfan Alias Farhan; Noordin Saleem, Siti Nur Dini; Nawam, Muhammad Zaid; Md Noh, Noriffah; Herawan, Safarudin Ghazali; Hussain, Faridah (Penerbit Akademia Baru, 2022)
Although, the effect of mass flow rate and solar irradiance variation is present in literature, it is still of significant interest to investigate the extent of the effect especially when utilizing a custom absorber design. In this paper, the effect of changing the mass flow rate and solar irradiance on the performance and temperature uniformity of a PVT using a custom spiral absorber design is simulated using ANSYS CFD software. By increasing the mass flow rate, the temperature uniformity and the performance parameters such as the average PV temperature, water outlet temperature, thermal and electrical efficiency all increase. By increasing the irradiance level, performance and temperature uniformity drop albeit at a smaller degree compared to change observed in mass flow rate variation. Amongst the tested range, the optimum mass flow rate and solar irradiance levels for best performance are 40 kg/h and 800 – 1000